2006
DOI: 10.1038/sj.bjc.6603378
|View full text |Cite
|
Sign up to set email alerts
|

TIMP-1 gene deficiency increases tumour cell sensitivity to chemotherapy-induced apoptosis

Abstract: Tissue inhibitor of metalloproteinases-1 (TIMP-1) is one of four inhibitors of the matrix metalloproteinases, which are capable of degrading most components of the extracellular matrix. However, in recent years, TIMP-1 has been recognised as a multifunctional protein, playing a complex role in cancer. In this regard, several studies have demonstrated an antiapoptotic effect of TIMP-1 in a number of different cell types. Since chemotherapy works by inducing apoptosis in cancer cells, we raised the hypothesis th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(60 citation statements)
references
References 21 publications
4
55
0
1
Order By: Relevance
“…More recently, we have shown that TIMP-1 immunoreactivity in the cancer cells is significantly associated with benefit from adjuvant anthracycline treatment in patients with primary breast cancer [15]. These clinical findings have also been supported by in vitro cell studies [16,17]. For example, murine fibrosarcoma cells deficient of the TIMP-1 gene were shown to be considerably more sensitive to chemotherapy compared with their genetically identical wild-type controls [16].…”
Section: Introductionsupporting
confidence: 61%
See 2 more Smart Citations
“…More recently, we have shown that TIMP-1 immunoreactivity in the cancer cells is significantly associated with benefit from adjuvant anthracycline treatment in patients with primary breast cancer [15]. These clinical findings have also been supported by in vitro cell studies [16,17]. For example, murine fibrosarcoma cells deficient of the TIMP-1 gene were shown to be considerably more sensitive to chemotherapy compared with their genetically identical wild-type controls [16].…”
Section: Introductionsupporting
confidence: 61%
“…These clinical findings have also been supported by in vitro cell studies [16,17]. For example, murine fibrosarcoma cells deficient of the TIMP-1 gene were shown to be considerably more sensitive to chemotherapy compared with their genetically identical wild-type controls [16]. Likewise, transfected MCF10A cells overexpressing TIMP-1 were less sensitive to adriamycin compared with non-transfected cells [17].…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…44,[73][74][75][76] Accordingly, we found that TIMP-1 deficiency, but not TIMP-2 deficiency, enhanced airway re-epithelialization implying that the regulation of matrilysin-mediated cell spreading and migration is specific to TIMP-1 and is not a generalized process among different members of the TIMP family. Although TIMP-1 can modulate cell apoptosis, survival, and proliferation through MMP-independent mechanisms, 25,77,78 we conclude that the moderating effect TIMP-1 confers on epithelial regeneration is a consequence of its ability to block MMP activity, specifically that of matrilysin. Indeed, the phenotype was reversed when a hydroxamate MMP inhibitor or matrilysin inhibitory antibody was added to wounded Timp1 Ϫ/Ϫ ALI cultures suggesting that TIMP-1 moderates re-epithelialization through MMP inhibition, specifically matrilysin.…”
Section: Discussionmentioning
confidence: 98%
“…Recent studies have shown that elevated levels of TIMP-1 in plasma or serum may give rise to endocrine resistance in metastatic breast cancer (Lipton et al, 2008). In vitro and in vivo studies have also suggested that a high level of TIMP-1 protects tumour cells against chemotherapy-induced apoptosis (Davidsen et al, 2006;Schrohl et al, 2006). Data presented by Ejlertsen et al (2010) at SABCS (2008) suggested that TIMP-1 and TOP2A collectively predict response to anthracycline therapy.…”
Section: Other Potential or Emerging Markersmentioning
confidence: 99%